Competition and Facilitation Effects of Semi-Natural Habitats Drive Total Insect and Pollinator Abundance in Flower Strips - Schoch, Kevin; Tschumi, Matthias; Lutter, Stefan; Ramseier, Hans; Zingg, Silvia (Frontiers in Ecology and Evolution, 2022)
Flower strips are an effective agri-environmental measure to promote functional biodiversity and ecosystem services in agricultural landscapes. In particular, tailored annual flower strips are increasingly implemented to foster insect pollination and biological pest control. While positive effects of flower strips on service providers and associated ecosystem services were recently demonstrated, little is known about how their effectiveness is affected by the surrounding landscape. We investigated how landscape composition and configuration, as well as flower strip traits influence the abundance of all insects, pollinators and natural enemies in 74 annual flower strips across 7 years (2014–2020). Landscape characteristics such as crop diversity, mean field size, area, and quality of semi-natural farmland habitats were assessed in a 1-km radius surrounding flower strips and combined with flower strip traits such as size, flower coverage, and flowering plant species richness to model insect abundance and diversity. Total insect and pollinator abundance, as well as wild bee abundance, richness, and diversity in flower strips were negatively affected by the share of semi-natural farmland habitats in the surrounding landscape, suggesting a dilution effect. On the other hand, semi-natural habitats with elevated ecological quality (i.e., biodiversity promotion areas with high botanical and structural diversity) enhanced total insect and pollinator abundance in flower strips. Furthermore, pollinator abundance and wild bee abundance in specific were positively affected by the flower coverage of the strips. Our results therefore suggest simultaneous competition and facilitation effects of semi-natural habitats on the landscape scale depending on their ecological quality. Annual flower strips will therefore be most effective in fostering services in landscapes of moderate to low complexity but with a high share of semi-natural habitats with increased ecological quality. For additional benefits for pollinator and wild bee abundance, flower strips should be designed to yield high flower cover. Our study thus highlights the importance of quality of ecological infrastructure and provides recommendations to maximize ecosystem services and biodiversity by means of flower strips at the landscape scale.